INTRODUKSI TENTANG LITERASI TATA KELOLA KEUANGAN TERINTEGRASI DENGAN FINANCIAL DIGITAL BAGI PELAKU UMK DI KECAMATAN MRANGGEN KABUPATEN DEMAK - Aprih Santoso; Ardiani Ika Sulistyawati; Saifudin Saifudin (LPPM Universitas Bina Bangsa, 2023)
The current condition based on the pre-survey of the Community Service Team, many members of the MSE Actors of Mranggen District are unable to manage their MSE finances properly, especially in managing receipts and expenses and separating personal finances from finances for business. On the one hand, reduced revenues due to the global food crisis have an impact on irregular income for MSEs. On the other hand, increased expenditure, due to the needs and prices of consumer goods also makes it difficult to manage MSE finances. This is the background of the Community Service Team to be interested in doing community service for members of MSE Actors in Mranggen District. Community Service Method with introductory training on financial governance literacy integrated with digital financial and mentoring. As a result of the service, MSE actors understand and are able to carry out MSE financial management that is integrated with digital finance neatly and well